An Islamic Concept of News (American Journal of Islam and Society, 1986)
IntroductionThe Islamic canons on news are deeply rooted in divine inspiration,whereas Western or Western-influenced laws and regulations are usually productsof human organhtions and individuals. Sandman, Rubin, and Sachsmanclassified the restrictions controlling news under: self-control, internal control,monopoly control, advertiser control, source control, and governmentor public control.Islamic guidelines are derived specifically from the divine revelationreceived by the Prophet of Islam, Muhammad (PBUH), fourteen centuriesago. Muslims believe that the Creator knows best about human nature.Therefore only He can provide His creatures with the most appropriateguidance to attain felicity both in this life and the next.‘ Since the ProphetMuhammad is the seal of the divine messenger, however, one may wonderhow guidance revealed fourteen centuries ago could survive all the changesoccuring since its revelation.In fact, although the Holy Qur’an and the Sunnah cover all aspects oflife, they are not confined to rigid details nor, except in a few areas, do theyprohibit interpretation. These matters are generally regarded, from the Islamicviewpoint, as critical decisions for the welfare of human beings regardlessof where or when they live. Examples of these matters are capital punishment,adultery, and theft. Even in these cases, the Holy Qur’an and the Sunnahdo not lay out detailed jurisdictional prescriptions for implementation.Jurisdiction and procedure are left to the judge, whose responsibility is to ...